Jasmonates and abscisic acid influence fruit ripening and plant water use: practical, physiological and morphological aspects - Soto Salinas, Alvaro Hernan <1983> (Alma Mater Studiorum - Università di Bologna, 2011)
The aim of the present thesis was to better understand the physiological role of the phytohormones jasmonates (JAs) and abscisic acid (ABA) during fruit ripening in prospect of a possible field application of JAs and ABA to improve fruit yield and quality. In particular, the effects of exogenous application of these substances at different fruit developmental stages and under different experimental conditions were evaluated. Some aspects of the water relations upon ABA treatment were also analysed. Three fruit species, peach (Prunus persica L. Batsch), golden (Actinidia chinensis) and green kiwifruit (Actinidia deliciosa), and several of their cvs, were used for the trials. Different experimental models were adopted: fruits in planta, detached fruit, detached branches with fruit, girdled branches and micropropagated plants. The work was structured into four sets of experiments as follows: (i) Pre-harvest methyl jasmonate (MJ) application was performed at S3/S4 transition under field conditions in Redhaven peach; ethylene production, ripening index, fruit quality and shelf-life were assessed showing that MJ-treated fruit were firmer and thus less ripe than controls as confirmed by the Index of Absorbance Difference (IAD), but exhibited a shorter shelf-life due to an increase in ethylene production. Moreover, the time course of the expression of ethylene-, auxin- and other ripening-related genes was determined. Ripening-related ACO1 and ACS1 transcript accumulation was inhibited though transiently by MJ, and gene expression of the ethylene receptor ETR2 and of the ethylene-related transcription factor ERF2 was also altered. The time course of the expression of several auxin-related genes was strongly affected by MJ suggesting an increase in auxin biosynthesis, altered auxin conjugation and release as well as perception and transport; the need for a correct ethylene/auxin balance during ripening was confirmed. (ii) Pre- and post-harvest ABA applications were carried out under field conditions in Flaminia and O’Henry peach and Stark Red Gold nectarine fruit; ethylene production, ripening index, fruit quality and shelf-life were assessed. Results show that pre-harvest ABA applications increase fruit size and skin color intensity. Also post-harvest ABA treatments alter ripening-related parameters; in particular, while ethylene production is impaired in ABA-treated fruit soluble solids concentration (SSC) is enhanced. Following field ABA applications stem water potential was modified since ABA-treated peach trees retain more water. (iii) Pre- and post-harvest ABA and PDJ treatments were carried out in both kiwifruit species under field conditions at different fruit developmental stages and in post-harvest. Ripening index, fruit quality, plant transpiration, photosynthesis and stomatal conductance were assessed. Pre-harvest treatments enhance SSC in the two cvs and flesh color development in golden kiwifruit. Post-harvest applications of either ABA or ABA plus PDJ lead to increased SSC. In addition, ABA reduces gas exchanges in A. deliciosa. (iv) Spray, drench and dipping ABA treatments were performed in micropropagated peach plants and in peach and nectarine detached branches; plant water use and transpiration, biomass production and fruit dehydration were determined. In both plants and branches ABA significantly reduces water use and fruit dehydration. No negative effects on biomass production were detected. The present information, mainly arising from plant growth regulator application in a field environment, where plants have to cope with multiple biotic and abiotic stresses, may implement the perspectives for the use of these substances in the control of fruit ripening.